Antioxidant Effects of Swimming Training and Curcumin in Withdrawal Period of Alcohol Overdose in Rats - Asiye Seyed; Sirous Farsi; Seyed Ali Hosseini; Gholamreza Kaka (Fasa University of Medical Sciences, 2018)
Background & Objective: Alcohol overdose can induce increment in free radicals. The present study aimed to  investigate the effect of swimming training and Curcumin in withdrawal period of alcohol overdose on superoxide dismutase (SOD), glutathione peroxidase (GPX), total antioxidant capacity (TAC), malone dealdeid (MDA) and protein carbonyl (PC) of rats. Materials & Methods: 40 rats were selected and administered alcohol every 8 hours for 4 days. Then they were subjected to the withdrawal of alcohol for six days and in seventh day divided in 5 groups of 8 rats (1) control (2) Curcumin (3) swimming training (4) Curcumin and swimming training (5) sham. Groups 3 and 4 swam 5 sessions per week for 2 weeks and groups 2 and 4 used Curcumin 5 times per week for 2 weeks peritoneally. For statistical analysis of data two-way ANOVA was used (p≤0.05). Results: Swimming training had significant effect on increase of SOD (p=0.001), GPX (p=0.001) and TAC (p=0.009) and reduction of MDA (p=0.001) and PC (p=0.001) of rats. Curcumin had significant effect on increase of SOD (p=0.001) and GPX (p=0.001) and reduction of MDA (p=0.001) and PC (p=0.001) of rats but had no significant effect on TAC (p=0.34) also Curcumin and swimming training had interactive effects on increase of SOD (p=0.001) and GPX (p=0.001) and reduction of PC (p=0.009) of rats but had no interactional effect on TAC (p=0.48) and MDA (p=0.13). Conclusion: Probably, swimming training and curcumin can be applied simultaneously in withdrawal period of alcohol overdose to increase antioxidant factors.